Some Fixed Point Theorems in Banach Spaces and its Applications - Lahrech, Salah; Laouini, Ala Eddine (My University, 2017)
In this work, we have studied a some of theorems related to fixed point and we have distinguished three cases: fixed point theorems for expansive mappings, and fixed point theorems for a sum of two mappings, one of which is expansive. in addition, common fixed point theorems for expansion mappings. In the latter, we applied one of these theorems on differential equations with a delay and integral equations with a delay to prove the existence and uniqueness of solution.Dans ce travail, nous avons étudié un ensemble de théories liées au point fixe et nous avons distingué trois cas : théorèmes de points fixes pour des applications expansive, et des théorèmes de points fixes pour un somme de deux applications, dont l'une est expansive. En plus des théories communes des points fixes pour les applications d'expansion. Dans ce dernier cas, nous avons appliqué une de ces théories sur les équations différentielles retardées et les équations intégrales retardées pour prouver l'existence et l'unité de la solution
memoire master mathematique
Keywords: Banach space - fixed point - expansive mappings - contraction mappings.; Espace de Banach - point fixe - applications expansive - applications contraction